Age Friendly Emergency Medicine Services: Integrating What Matters, Medications, Mobility, and Mentation into Emergency Response. (20th December 2022) - Taylor, Kate; Wagner, Teresa
Abstract: Background: Our population is aging. The Age Friendly Health System (AFHS) initiative by the Institute of Healthcare Improvement (IHI) includes the 4 M's of What Matters, Medications, Mobility, and Mentation, and is at the forefront of older adult health care. When applying the 4M's to emergency medical services (EMS), the benefits include avoiding unnecessary transports and helping the patient stay healthy and safe in their home setting. The University of North Texas Health Science Center and other partnerships aspired to designate MedStar the first AFHS in the country within EMS practice. Method: The Plan‐Do‐Study‐Act (PDSA) cycle aimed at various changes with the AFHS components of What Matters and Medications within an electronic medical record (EMR) algorithm for emergency medical paramedics. Additionally, previously piloted geriatric practice leadership institute projects embedded Mentation and Mobility by including specific screenings in the EMR. Result: The preliminary result in the PDSA described showed 52% of older adults answered health when asked What Matters most to them today. However, updated data as of January 2022, showed an overwhelming 6732 (69%) patients out of 9685 patients, answered health when asked What Matters most to them today. Additionally, the EMR identifies high‐risk medications. Paramedics can now verify potential risks and develop a care plan based on the identified high‐risk medications. Conclusion: Implementing AFHS components allows for better care delivery and outcomes as our older population is growing and embraces more complexities. The data is still novel but promising, requiring longitudinal information before conclusions can be considered. IHI is currently reviewing opportunities to expand its models of care into emergency medicine, behavioral health, and other settings. MedStar sets the example that EMS can practice the AHFS approach serving as a model for the EMS environment. We are currently awaiting feedback from IHI regarding our request to designate MedStar the first AFHS EMS practice in the country.